Catalysis : from principles to applications - Beller, Matthias; Renken, Albert, 1941-; Santen, R. A. van (Rutger A.) (New York : Wiley, 2012)
"This advanced textbook ... covers all the essential principles, ranging from catalytic processes at the molecular level to catalytic reactor design and includes several case studies illustrating the importance of catalysts in the chemical industry."--page 4 of cover